Combining ability studies in Sesame (Sesamum indicum L.) - S.Ranjith Rajaram and P.Senthil Kumar (Electronic Journal of Plant Breeding, 2011)
An attempt was made to study the general and specific combining ability in sesame (Sesamum indicum L.) through L X Tanalysis with ten lines and four testers. Eight characters viz., days to 50 per cent flowering, plant height, number of branches perplant, number of capsules per plant, capsule length, number of seeds per capsule, 1000 seed weight and seed yield per plant werestudied. Based on the general combining ability effects of parents IVTS-14-07 [L6] was found to be a good general combiner fordays to 50 per cent flowering and number of capsules per plant, IVTS-215-06 [L10] was found to be good general combiner forplant height, number of branches per plant and 1000 seed weight. IVTS-24-06 [L9] was found to be good general combiner fornumber of seeds per capsule and seed yield per plant. The cross combination IVTS -17-07 X TMV 4 [L5 X T2] showed negative,significant sca for days to 50 per cent flowering. AVTS-3-06 X TMV 3 [L4 X T1] exhibited positive and significant sca fornumber of capsules per plant and seed yield per plant and hence recommended for yield improvement.